Needs Analysis of Agricultural English Teaching in an Indonesian Islamic Higher Education Context - Muhammad Yunus; Sitti Halijah (Tamaddun Life, 2021)
The research is the development of Agricultural English teaching materials at Universitas Muslim Indonesia. The purposes of this research are to (1) produce a type of Agricultural English teaching material suitable to be used by the students of Faculty of Agriculture UMI and to (2) discover why the students are learning English. The method used is research and development. The research site was at the Faculty of Agriculture UMI with the number of 50 respondents. The results showed that based on the student responses, 12 out of 42 topics occupy the highest percentage needed for Agricultural English teaching materials. Those 12 topics are as follows: rice, tomatoes, chili, shallots, eggplant, papaya, rambutan, coconut, coffee, land, disease pest, and seeds. Then, the purposes of the students learning English can be categorized into two major groups, namely to anticipate competition in the workplace where the ability to communicate both oral and written is needed and to prepare themselves in the academic field both to complete S1 (undergraduate degree) and to continue their studies S2 (master degree).